Effect of Dy substitution in the giant magnetocaloric properties of HoB2. Issue 1 (31st January 2020) - Castro, Pedro Baptista de; Terashima, Kensei; Yamamoto, Takafumi D.; Iwasaki, Suguru; Matsumoto, Ryo; Adachi, Shintaro; Saito, Yoshito; Takeya, Hiroyuki; Takano, Yoshihiko
ABSTRACT: Recently, a massive magnetocaloric effect near the liquefaction temperature of hydrogen has been reported in the ferromagnetic material HoB2 . Here we investigate the effects of Dy substitution in the magnetocaloric properties of Ho1- x Dy x B2 alloys ( x = 0, 0.3, 0.5, 0.7, 1.0). We find that the Curie temperature ( T C ) gradually increases upon Dy substitution, while the magnitude of the magnetic entropy change |Δ S M | and adiabatic temperature change Δ T ad showed a gradual decrease. On the other hand, due to the presence of successive transitions in these alloys, the peak height of the above magnetocaloric properties tends to be kept in a wide temperature range, leading to a relatively robust figure of merit in a wide temperature span. These alloys could be interesting candidates for magnetic refrigeration in the temperature range of 10–60 K. Graphical abstract: uf0001